CASH FLOW ACCOUNTING INFORMATION SYSTEM AS INTERNAL CONTROL AT WATES VILLAGE (Lembaga Pengembangan Kinerja Dosen, 2022)
The development of information technology is currently growing rapidly, where almost all have used and developed information systems in such a way that they are able to advance and develop their business well. The existence of a good information system will produce information according to needs. Good information is information that can be presented in a timely manner, useful and reliable. One of the important information systems in an institution or agency is the Accounting Information System. Along with the increasingly rapid development, the use of computers plays an important role in various fields that support each other in aspects of life. This includes financial data and information processing systems that cannot be separated from everyday life. Because without a financial data and information processing system, activities within an organization, company or agency will not run smoothly as expected, both in terms of time and accuracy and speed of the resulting performance. This becomes an obstacle to the activities and implementation of existing activities in an organization, company or agency. Recording cash flows using books is considered less effective in terms of time and accuracy. Recording that must be done many times sometimes causes some errors so that there is often a difference between the real balance and the cash book. Keywords: System, Information, Accounting, Cash Flow